2021
DOI: 10.1021/acs.est.1c04421
|View full text |Cite
|
Sign up to set email alerts
|

Solution 31P NMR Investigation of Inositol Hexakisphosphate Surface Complexes at the Amorphous Aluminum Oxyhydroxide–Water Interface

Abstract: Phytate (myo-inositol hexakisphosphate, myo-IHP) is one of the most common organic phosphorus (P) species in soils and sediments which can be mineralized to increase the concentration of dissolved phosphate in pore water. Because of its six phosphate functional groups, functional group-specific adsorption mechanisms in reactive soil minerals become important in predicting solubility. In this study, solution 31 P NMR was used to elucidate the functional groupspecific adsorption mechanisms of myo-IHP at the amor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…The peaks assigned to vibrations of −COO – of the vivianite-OA complex underwent a blue shift to 1426 and 1616 cm –1 (Figure A), indicating the formation of inner-sphere surface complexes on the vivianite surface through chemisorption. This blue shift of Raman characteristic peaks caused by inner coordination has been well reported. ,, In this study, the blue shift of −COO – peaks in CA before and after adsorption indicated the formation of surface complexes through chemisorption (Figure B). It was noteworthy that the peaks at 1407 and 1597 cm –1 , assigned to the symmetric and asymmetric vibrations of −COOH at pH 4.0 and 6.0, respectively, disappeared when the pH increased to 8.0 because of CA deprotonation.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The peaks assigned to vibrations of −COO – of the vivianite-OA complex underwent a blue shift to 1426 and 1616 cm –1 (Figure A), indicating the formation of inner-sphere surface complexes on the vivianite surface through chemisorption. This blue shift of Raman characteristic peaks caused by inner coordination has been well reported. ,, In this study, the blue shift of −COO – peaks in CA before and after adsorption indicated the formation of surface complexes through chemisorption (Figure B). It was noteworthy that the peaks at 1407 and 1597 cm –1 , assigned to the symmetric and asymmetric vibrations of −COOH at pH 4.0 and 6.0, respectively, disappeared when the pH increased to 8.0 because of CA deprotonation.…”
Section: Resultssupporting
confidence: 85%
“…This blue shift of Raman characteristic peaks caused by inner coordination has been well reported. 6,64,65 In this study, the blue shift of −COO − peaks in CA before and after adsorption indicated the formation of surface complexes through chemisorption (Figure 6B). It was noteworthy that the peaks at 1407 and 1597 cm −1 , assigned to the symmetric and asymmetric vibrations of −COOH at pH 4.0 and 6.0, 66 The blue shift of the −COO − peak in Raman spectra was due to the formation of an inner-sphere surface complex through chemisorption, indicating that −COO − significantly altered the interfacial hydration environment on a vivianite surface, thus reducing the energy barrier required for pit dissolution, thereby accelerating the release of iron and phosphorus.…”
Section: Molecular Adsorption Mechanism Of Organicmentioning
confidence: 50%
“…11,58 Besides, phytate stability varies with metal oxides, especially amorphous Fe and Al. 78 For example, phytate is sorbed onto goethite via four of the 6-phosphate groups, with the remaining two being free. 68 This explains the 3:2 sorption ratio between phytate and P in soils.…”
Section: Phytate In Soilsmentioning
confidence: 99%
“…Proteins like phytase bear multiple functional groups and are known to interact with mineral surfaces via, for example, electrostatic interaction, hydrophobic interaction, van der Waals force, and conformational entropy. ,, Therefore, a similar kinetics experiment was conducted between phytase-reacted calcite and phytic acid (i.e., calcite-phytase and InsP6 (aq) , Figure B–D), and the results showed impaired P mineralization. With multiple phosphate groups and thus strong chelating ability, phytic acid also actively interacts with clay minerals like calcite. Therefore, another kinetics experiment between phytic acid-reacted calcite and phytase was conducted (i.e., calcite-InsP6 and phytase­(aq) , Figure B–D), and inhibited phytase activity was observed. Although P mineralization was suppressed for all three addition sequences, released [phosphate] generally followed the order calcite-phytase and InsP6 (aq) > calcite-phytase-InsP6 > calcite-InsP6 and phytase (aq) , indicating that calcite–phytase interaction did not affect the catalytic ability of phytase as much as the calcite–phytic acid interaction.…”
Section: Resultsmentioning
confidence: 99%